Ethical Challenges in Nanometrology - Stefan Luby; Martina Lubyova; Ivan Kostic; Pavol Hrkut (Communications - Scientific letters of the University of Zilina, 2018)
Nanometrology is an intrinsic and fast developing part of nanoscience. Given the huge diversity of nanostructures ranging from large molecules from about 10 atoms to structures from 105 atoms (particles of the size ≤ 100 nm), broader investigations in this area cannot be exactly scrutinized nor repeated by the existing capacities. This gave rise to the initiative for reproducibility that aims to avoid simplified approaches, plagiarism and other phenomena that are often triggered by the “publish or perish” philosophy, as well as business practices of predatory journals. In this paper, we discuss two case studies illustrating how to solve these problems: a study of the structural stability of nanoparticles by three complementary methods, and a design of reliable nanoparticle gas sensors used in environment or medicine.